The use of ICT’s in the COVID-19 pandemic: pedagogical coordinators and teachers between commitment and chaos - dos Santos , Michele Serafim; Rebolo, Flavinês (Seven Editora, 2023)
This article aims to reflect on the use of information and communication technologies - ICTs by teachers and pedagogical coordinators of the public education network, considering the current scenario of the Covid-19 Pandemic and reports the experiences as a teacher and coordinator of the Public Network of Education in the state of Mato Grosso do Sul. The text is divided into two parts: the first presents a contextualization of teacher training and the use of ICTs in the Covid-19 Pandemic; the second presents the account of experiences and practices as a teacher and coordinator of the public education network during the pandemic period. We sought to dialogue with theorists to promote reflections on issues observed during the challenges of the work of teachers and pedagogical coordinators in the pandemic period, in which these professionals exercised and exercise numerous functions inside and outside the school unit, as they feel unmotivated, helpless, and frustrated in their work.DOI: https://doi.org/10.56238/devopinterscie-056